Learning culture to organizational breakthroughs in Malaysian companies. - Khajeh, Hossein Bodaghi; Che Rose, Raduan; Kumar, Naresh; Mohd Salleh, Lailawati (2011)
Malaysian society has been revolutionized. The level of education in a large proportion of the population increased and Malaysians’ quality of life has been improved. In order to meet a new economy climate, the national mission’s aims encompass on nation's global competitiveness, human capital development, national integration, ethnic relations, distribution of income and wealth, and the quality of life. For achieving aforementioned aims Malaysian companies needs to achieve better performance and plays an unprecedented role toward promoting learning culture. Rich literature has been reviewed in the area of the learning organization and learning culture. So far, the researchers have not captured any detailed incentives reported in Malaysian context pertaining to the links between Watkins and Marsick’s dimensions and performance in listed Malaysian companies. Thus, this study aims to explore the relationships between learning organization dimensions, and change in financial and knowledge performance among Malaysian companies listed in Bursa Malaysia. Based on the theoretical framework proposed by Watkins and Marsick this study conducted dimensions of learning organization questionnaires survey, in 400 Malaysian companies listed in Bursa Malaysia and acquired a sample of 218 companies. Findings of research provide empirical evidence, which supports the concept of the learning organization and their positive influence on the knowledge and financial performance. The findings demonstrated that organizations with conducive learning culture, has charismatic and dedicated leaders are able to grow in their knowledge and financial performance.